2013
DOI: 10.1021/jp405097c
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Bond-Breaking Electron Transfer in Mixed Water–Ethylene Glycol Solutions: Reorganization Energy and Interplay between Different Solvent Modes

Abstract: We explore solvent dynamics effects in interfacial bond breaking electron transfer in terms of a multimode approach and make an attempt to interpret challenging recent experimental results (the nonmonotonous behavior of the rate constant of electroreduction of S2O82– from mixed water–EG solutions when increasing the EG fraction; see Zagrebin, P.A. et al. J. Phys. Chem. B2010, 114, 311). The exact expansion of the solvent correlation function (calculated using experimental dielectric spectra) in a series predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Recent experimental studies of the influence of solvent dynamics on electrochemical electron transfer reactions have led to some challenging observations. Such effects were discussed on the basis of Sumi–Marcus model and Brownian dynamics combined with quantum chemical approaches. Another class of reactions of great fundamental and practical interest is electron transfer in solids.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental studies of the influence of solvent dynamics on electrochemical electron transfer reactions have led to some challenging observations. Such effects were discussed on the basis of Sumi–Marcus model and Brownian dynamics combined with quantum chemical approaches. Another class of reactions of great fundamental and practical interest is electron transfer in solids.…”
Section: Discussionmentioning
confidence: 99%
“…EG and EG–water mixtures have another important application field. Such solvents are used as a media with variable viscosity in experimental studies of the solvent dynamics effect on electrochemical reactions (see, for example [3,4] ). In the framework of modern quantum mechanical theory of electron transfer some quantities which affect reaction kinetics (effective frequency factor, solvent reorganization energy) can be calculated by using the complex dielectric spectrum of a polar medium measured experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Cellosolves are used as industrial and biological solvents, surfactants, detergents and wetting agents. Such solvents are also used as a media with variable viscosity in experimental studies of the solvent dynamics effect on electrochemical reactions [4,5]. Renewed interest in EG was recently found in the field of solvents for green and sustainable chemistry, where it was reported that EG can be used as a hydrogen bond donor to form…”
Section: Introductionmentioning
confidence: 99%